Education Using Spinning Clue Media on School-Age Children’s Aggregate Knowledge of Sexual Violence: Pra Experimental Study - Sri Ayu Rahayu Paneo; Hijrah; Endang Kurnia; Hasbullah (Citra Delima Scientific journal of Citra Internasional Institute, 2026)
Sexual violence against school-aged children is a serious problem that impacts children’s physical, psychological, social, and academic development. Children’s limited knowledge regarding bodily boundaries, forms of sexual violence, ways to refuse, and reporting mechanisms increases their vulnerability to sexual violence. This study aims to analyze the effect of education using the Spinning Clue media on improving the aggregate knowledge of school-aged children regarding sexual violence at UPT SPF SD Inpres Maccini I/1. This study is based on the concepts of health education, knowledge theory, the developmental characteristics of school-aged children, and interactive learning media. The method used is quantitative with a quasi-experimental design using a one-group pre-test post-test model. The sample consisted of 40 students in grades 1–3 selected through purposive sampling. The research instruments included a sexual violence knowledge questionnaire and the Spinning Clue media, which contained material on private body parts, forms of sexual violence, refusal strategies, and reporting to a trusted adult. Data analysis used the Wilcoxon Signed Ranks Test. The results showed that before the education, respondents’ knowledge was categorized as good for 21 students (52.5%), adequate for 17 students (42.5%), and insufficient for 2 students (5%). After the education, all respondents were categorized as good (40 students, 100%). The average score increased from 10.70 to 14.90 with a p-value = 0.000. In conclusion, education using the Spinning Clue medium has a significant effect on increasing school-age children’s knowledge about sexual violence and can be used as a preventive educational strategy in elementary schools.